When Private and Public Policing Merge: Thoughts On Commercial Policing - Mulone, Massimiliano (Social justice, 2011)
The article looks at the privatization and commoditization of security services, as of 2011, focusing on public police forces' sale of security-related services to private parties, termed commercialization of police services. The author discusses his 2008 study of the practice by the Montreal (Quebec) Police (SPVM). He says the policy was motivated by the police force's desire to maintain and expand its operations in the face of budget constraints. He outlines the kinds of services the SPVM provides and the revenue generated from them. He discusses issues raised by the practice, including potential inequality in the social provision of security based on ability to pay and conflicts between traditional definitions of the police officer's role versus the demands of SPVM customers.